2009
DOI: 10.1021/jp809746a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms of the Methylation of Ethene with Methanol and Dimethyl Ether over H-ZSM-5: An ONIOM Study

Abstract: The mechanisms of ethene methylation with methanol and dimethyl ether have been investigated using a 128T cluster of ZSM-5 zeolite modeled by ONIOM(B3LYP/6-31G(d,p):UFF) and ONIOM(M06-2X/6-311+G(2df,2p):UFF) calculations. The effects of the infinite zeolitic framework on the model of the zeolite nanopocket, which consisted of a quantum cluster of 34 tetrahedral units and of 128 tetrahedral units modeled on the UFF level, were also included. The zeolitic Madelung potential was reproduced by a set of point charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
131
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 83 publications
12
131
0
1
Order By: Relevance
“…Also, the absolute reaction rates could be calculated with near chemical accuracy, and the qualitative experimental trends were well reproduced. Finally, the intrinsic barrier for direct methylation of ethene has been reported to be 121 kJ/mol in an ONIOM study on H-ZSM-5 [28]. The barriers reported in these three studies agree well with experimental data: 109, 69, and 45 kJ/mol has been measured for the methylation of ethene, propene, and t-2-butene, respectively (see below).…”
Section: Insights From Quantum Chemical Investigationssupporting
confidence: 68%
See 2 more Smart Citations
“…Also, the absolute reaction rates could be calculated with near chemical accuracy, and the qualitative experimental trends were well reproduced. Finally, the intrinsic barrier for direct methylation of ethene has been reported to be 121 kJ/mol in an ONIOM study on H-ZSM-5 [28]. The barriers reported in these three studies agree well with experimental data: 109, 69, and 45 kJ/mol has been measured for the methylation of ethene, propene, and t-2-butene, respectively (see below).…”
Section: Insights From Quantum Chemical Investigationssupporting
confidence: 68%
“…When employing cluster calculations, this reaction is invariably found to be quite endothermic, the values of the reaction energy range from ?43 to ?57 kJ/mol [13, 21-23, 26, 30]. Employing more sophisticated ONIOM methods, Maihom et al [28] also found a similar value; ?66 kJ/mol. Thus, these computational studies indicate that the formation of methoxy groups from methanol or DME is an endothermic reaction.…”
Section: Insights From Quantum Chemical Investigationsmentioning
confidence: 90%
See 1 more Smart Citation
“…The products, propene and ethene, are eliminated from the side chain of the aromatic benzene derivative by an internal H-shift step. Two different pathways have been reported for the methylation step in the literature [36][37][38]: a stepwise mechanism that involves a surface-bound methoxide intermediate, and a concerted one in which adsorbed methanol directly attacks the substrate to be methylated. The concerted pathway is widely used in theoretical calculations because the experimental kinetic measurements are readily explained by this pathway [19,37,39], so we adopted this mechanism in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…As far as the mechanism of the zeolite-catalyzed methylation reaction is concerned, two different proposals have been advocated in literature: a stepwise route that involves a surfacebound methoxy group intermediate, and a concerted mechanism in which physisorbed methanol directly interacts with the species to be methylated [22,26,27]. While spectroscopic evidence for the existence of surface-bound methoxy groups has been presented, and the fundamental viability of a stepwise mechanism has been verified, experimental kinetic measurements are readily explained by the concerted pathway [26,28].…”
mentioning
confidence: 99%